Missing Children - Donna Davis (EDIS, 2009)
FAR-0100, a 2-page transcript of the Family Album Radio Program broadcast by Donna Davis, presents data from a report from the Department of Justice about the number of incidences of missing, abducted, runaway and throwaway children to help parents put the risk of abduction into perspective. Published by the UF Department of Family Youth and Community Sciences, March 2009.